Study of Sub-Acute Toxicity Profile of Fenugreek (Trigonellafaenum-Graecum) Seeds in Kidney Tissues of Albino Rat: A Randomized Control Trial (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2019)
Background : The objective of the present study was to evaluate the sub-acute toxic effects of ethanol extract of fenugreek seeds on kidney tissues of albino rats.Materials and methods: The present study was conducted on 30 albino rats divided into Group A, B, C, D and R. Group A (Control group) was treated with distilled water. Group B, Group C and Group D were treated orally with ethanol extract of fenugreek seeds at a dose of 1.25 gm/kg/day, 2.5 gm/kg/day and 5 gm/kg/day respectively for 90 consecutive days. Group R (Recovery group) was treated with seed extract of 5 gm/kg/day for 90 days followed by no treatment for next 28 days to observe any toxic effect if present in highest dose whether reversible or not. On 91st day all the animals of Group A, Group B, Group C and Group D were sacrificed and Group R was sacrificed on 119th day. Blood sample was collected from all the rats by cardiac puncture before sacrifice for measurement of biochemical and hematological parameters, and kidneys were collected for histopathological examination after sacrifice.Results: Upto 2.5 gm /kg/day dose level, all parameters of all experimental groups were statistically not significant when compared with control group. At 5 gm/kg/ day dose level the seeds extract produced statistically significant change in biochemical parameters such as serum creatinine and blood urea. In gross microscopic examination of kidney, at the highest dose level showed the sign of cell injury like cellular swelling, hemorrhage, inflammatory cells infiltration, necrosis etc. Interestingly, these biochemical and microscopic findings at the highest dose level were absent in recovery group.Conclusion: Finally, the study revealed that ethanol extract of fenugreek seeds was non toxic up to 2.5 gm/kg/day dose level and produce renal toxicity at 5 gm/kg/day dose level in sub acute toxicity test. So, if needed to use in higher therapeutic dose the toxicity profile of seeds extract must be re-evaluated.Chatt Maa Shi Hosp Med Coll J; Vol.18 (1); Jan 2019; Page 36-43